Theory and Practice in the Interdisciplinary Production and Reproduction of Scientific Knowledge ID in the XXI Century - Pombo, Olga; Gärtner, Klaus; Jesuíno, Jorge (Logic, Argumentation & Reasoning, Interdisciplinary Perspectives from the Humanities and Social Sciences, 2023)
XX, 309 p. 1 illus.